Pendidikan Kesehatan PENDIDIKAN KESEHATAN DENGAN MEDIA ULAR TANGGA TERHADAP BENCANA BANJIR AIR DI SD NEGERI 82 PALEMBANG - Fina Winata; Apriyani Apriyani; Miranti Florencia Iswari (IKesT Muhammadiyah Palembang, 2024)
Background: Floods are traumatic events that put pressure on the mental health of disaster survivors. Flood disasters can cause damage to settlements, the economy and environment of an area, as well as loss of human life. Some of the causes of water flooding are high rainfall, littering, which prevents water from flowing in the gutter. One form of disaster education in increasing students' knowledge of flood disasters is by conducting health education about flood disasters by providing education through the medium of snakes and ladders. Objective: To find out the effect of health education using snakes and ladders media on flood disasters at SD Negeri 82 Palembang. Method: Pre-experimental research with a one group pre and post design using total sampling with a total of 33 respondents at SD Negeri 82 Palembang. Analysis was carried out using the alternative nonparametric Wilcoxon Sign Test. Results: It was found that the median knowledge value before the intervention was given was 6.00 and after the intervention was given the median value was 9.00, increasing by 3.00 with a p value of 0.001 <0.05. Conclusion: there is an influence of health education using snakes and ladders media on flood disasters at SD Negeri 82 Palembang between before and after being given health education.